Association between blood group and susceptibility to malaria and its effects on platelets, TLC, and Hb - Hira Burhan; Askari Syed Hasan; Syed Mansur-ul-Haque; Ghazanfar Zaidi; Taha Shaikh; Aisha Zia (Journal of Infection in Developing Countries)
Introduction: According to the World Health Organization, the estimated number of malaria cases in Pakistan is about 1.5 million. Hematological variables like platelets, total leukocyte count (TLC), and hemoglobin (Hb) need to be evaluated to diagnose malaria in suspects. This study aimed to investigate the association between blood group and susceptibility to malaria and effects on platelets, TLC, and Hb. Methodology: This was a case-control study with a sample size of 446, of which 224 were malarial cases and 222 were controls. A designated questionnaire was developed to know age, gender, malarial strain, Hb, TLC, platelets, and blood group. Results: Of 224 malarial cases, 213 were P. vivax, and 11 were P. falciparum. There were 58 patients with blood group A, 72 with group B, 69 were O and 23 were AB. There was no significant difference in the blood group of controls compared to malarial patients (p > 0.05). Mean Hb level was 11.5mg/dL in malaria patients and 12.5mg/dL in controls. There was significant difference (p<0.01) in the mean platelet count in malarial (11,7000/μL) and control (24,5000/μL) patients. All blood groups showed similar falls in Hb and platelet levels, showing no significant difference among blood groups (p = 0.79 and p = 0.52, respectively). TLC was not significant between malarial and control groups (p = 0.072). Males were two times susceptible to malaria. Conclusions: There was no significant association between the type of blood group and susceptibility to malaria or developing anemia or thrombocytopenia.